Preference pulses induced by reinforcement. Issue 3 (30th September 2014) - Hachiga, Yosuke; Sakagami, Takayuki; Silberberg, Alan
Abstract Eight rats responded on concurrent Variable‐Ratio 20 Extinction schedules for food reinforcement. The assignment of variable‐ratio reinforcement to a left or right lever varied randomly following each reinforcer, and was cued by illumination of a stimulus light above that lever. Postreinforcement preference levels decreased substantially and reliably over time when the lever that just delivered reinforcement was now in extinction; however, if that lever was once again associated with variable ratio, this decrease in same‐lever preference tended to be small, and for some subjects, not in evidence. The changes in preference level to the extinction lever were well described by a modified version of Killeen, Hanson, and Osborne's (1978) induction model. Consistent with this model's attribution of preference change to induction, we attribute preference change in this report to a brief period of reinforcer‐induced arousal that energizes responding to the lever that delivered the last reinforcer. After a few seconds, this induced responding diminishes, and the operant responding that remains comes under the control of the stimulus light cuing the lever providing variable‐ratio reinforcement.